Seismic Responses of Concrete Building Subjected to Out-of-phase Ground Motions - Yohanes Karyanto; Dario Rosidi; Pamuda Pudjisuryadi (Civil Engineering Dimension, 2023)
Seismic performance of a building is commonly evaluated by applying same design ground motions at each building foundation. However, local soil conditions beneath a building likely vary, and these variations could result in out-of-phased design ground motions at each of the foundation locations. In this study, building’s responses during earthquakes were analyzed and compared using same and out-of-phase ground motions. The building is 10-story, 90m-wide, reinforced concrete structure supported on isolated footings with tie beams. Dynamic time response analyses were performed using five earthquake records which were scaled to a design response spectrum for a location in Surabaya. Seismic modification factor, R, of 8 was used. The results indicate that the use of out-of-phase ground motions does not have significant impacts on building inter-story drifts; it results, however in significantly higher column base shears and tie beam axial forces compared to those calculated using same ground motions.